Agglomeration and Exports with Heterogeneous Firms: Evidence from Chinese Firm-level and County-level Data - Churen Sun; Zhihao Yu; Tao Zhang (European Regional Science Association (ERSA), 2012)
The paper proposes a model to investigate the influences of agglomeration on heterogeneous firms' exporting behaviors. In the model, firms are heterogeneous in productivity. Selection effect and agglomeration economies caused by agglomeration increase firms' productivity and decreases industrial entry costs, and factor prices are increased because of agglomeration. The former factors increase while the latter reduces firms' exporting possibilities and sales. The theoretical result shows that the compositive effect is that the influences of productivity on the latter increase with agglomeration level. Empirical results based on data from Chinese Industrial Enterprises between 1998 and 2007 verify the theoretical results. Moreover, the is a critical agglomeration level for each firm (which varies across firms' productivity), so that the influence of agglomeration on a firm' export increases with agglomeration if it's less than this level while decreases if it's larger than it. The paper also estimates the influences of local market effect, urban economies and competition effect on firms' exports and find that they affect firms' exporting behaviors in very complicated modes.
Keywords: 330